Paradoksal Pertunjukan Tari Pakarena Mabbiring Kassi Daeng Serang dakko (Dalam Perspektif Nilai) - M, - Rahma (Universitas Negeri Makassar, 2023)
In every region and culture, the art of dance has unique and distinctive characteristics that reflect local wisdom and noble values of the local community. Understanding the values of local wisdom, one of which is reflected in the art of dance, is very important for today's young generation because the young generation is the successor of local culture and identity in the future, while in the increasingly rapid era of globalization and modernization, the young generation is very easily tempted by foreign culture is considered more contemporary and trendy, so local values are often overlooked. The noble values of local wisdom in the art of dance can vary in each region and culture, but basically the art of dance always reflects and respects the uniqueness and local wisdom of the local community, this is also the case with the paradoxical Padengan dance performances, especially the Pakarena Mabbiring Kassi Daeng Serang Dakko which reflects the values of the Makassar ethnic community